PERILAKU PENGGUNA TERHADAP SISTEM GURU PEMBELAJAR ONLINE DI SEKOLAH MENENGAH PERTAMA NEGERI KOTA PALEMBANG - Fitria Apriani; Muhammad Izman Herdiansyah; Diana Diana (Jurnal Bina Komputer, 2019)
GPO (Online Learning Teacher) is a program developed by Kemdikbud post-UKG (Teacher Competency Exam) 2015 which aims to improve teacher competence. Learning Teachers Online mode consists of 3 (three) models: GP Full Dedicated Mode, GP Front Facing Mode and GP Combination Mode Mode. In the application of the GP program does not necessarily run as planned, while the conditions that occur in the field to meet the problems in the application, due to factors that affect users GP program itself, such as the use of information technology used is sometimes considered by some teachers as a difficulty due to lack of knowledge will be computer technology. Unified Theory of Acceptance and Use of Technology (UTAUT) states that one's acceptance of information technology (user intention). two variables of research that variables have significant effect to behavioral intention, effort expectancy have significant effect to behavioral intention and facilitating condition correlate positively to user behavior and three other variables that is social influence, no significant influence on behavioral intention and behavioral intention unrelated posistif with user interest User Behavioral) Online Teacher Learning System (GPO) system system of Junior High School teachers